Mitigation of Legal Disputes on Business Contracts between Commercial Banks and Providers of Information Technology Goods and Services - Gautama, Maria Patricia; Kanthika, I Made; Markoni; Zulfikar (GoAcademica Research & Publishing, 2024)
This research aims to translate Financial Services Authority Regulations into the clauses of business contracts between commercial banks and providers of information technology goods and services by harmonizing agreements with contractual law principles, especially to reach mutual agreements to mitigate legal disputes. The harmonization process starts from the planning, preparation, implementation, and contract termination stages. The research method used in this article is normative legal research, which aims to research, study, and analyze laws and regulations relating to banking, the OJK, and business contracts between banks and providers of information technology goods and services. This research will use several approaches, including a case approach, a statutory approach, and a conceptual approach. The results of this research emphasize the importance of banks providing standard business contracts that comply with the provisions in MRTI SEOJK to facilitate initial identification and the need for harmonization of clauses that require negotiation with information technology providers. In mitigation efforts, the Bank has considered to accept and control the risks after obtaining approval from management.